Bronchopleural Fistula after Surgery: Therapeutic Efficacy of Bronchial Occluders - Young Min Han (대한영상의학회지, 2021)
Purpose To evaluate the usefulness and effectiveness of bronchial occluders in the treatment of postoperative bronchopleural fistula (BPF). Materials and Methods The subjects of the study were six out of seven postoperative BPF patients who underwent surgery due to tuberculosis or lung cancer between 2009 and 2019. Each patient had a bronchial occluder inserted to treat BPF that occurred after surgery. Of the six patients, five had lung cancers and one had tuberculosis. Five were male and one was female; their ages ranged from 59 to 74 years, with an average of 69 years. The diagnosis of BPF was based on findings from bronchoscopy and CT, and treatment was initiated approximately 1 to 2 weeks after diagnosis. The technical and clinical success of the bronchial occluders in the treatment of BPF was evaluated. The study assessed the postoperative clinical effects of the occluders, survival duration, and additional treatments. Results All six patients were successfully treated. Clinical success was achieved in five patients, while partial clinical success was achieved in one; there was no clinical failure. No complications during the migration of the device or device perforations were observed. Two patients were diagnosed with BPF by CT, while four were diagnosed by bronchoscopy. Lobectomy, bilobectomy, and pneumonectomy were performed on two patients each. The periods between surgery and diagnosis ranged from 1 to 34 months; the average was 10 months. Four patients (59–103 days; an average of 80.5 days) died and two (313 days, 3331 days) survived. The causes of death were aggravation of the underlying disease (n = 2), pulmonary edema and pleural effusion (n = 1), and pneumonia (n = 1). Additional catheter drainage was performed in one patient, and a chest tube was maintained in two patients. Conclusion Bronchial occluders are useful and effective in the treatment of BPF after pulmonary resection.